Pengaruh Kompetensi Pedagogik dan Motivasi Kerja Guru terhadap Prestasi Belajar Siswa Kelas V SD di Kecamatan Langowan Timur (Jurnal Simki Pedagogia, 2025)
This study aims to analyze the influence of Pedagogical Competence and Teacher Work Motivation on the Learning Achievement of Grade V Elementary School Students in Langowan Timur District. This study used non-probability sampling with saturated sampling techniques, involving 75 students as samples. Data were analyzed using descriptive statistics, correlation, reliability, normality, linearity, simple regression, and multiple regression with the help of SPSS 25. The results showed that there was a significant direct influence of pedagogical competence on the learning achievement of grade V students p = 0.000